The Effect of Cu Doping on the Transformation from Rutile to Anatase and Cu Occupation Tendency in TiO2 Solid Solution - Jun-Yu Chen; Ji-Kang Yan; Guo-You Gan (Journal of Spectroscopy)
TiO2 doped with different amounts of Cu2+ ions (from 0 to 3 mol%) was synthesized by sol-gel method. The samples were characterized by X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). The XRD analysis showed that the Cu-doped TiO2 samples exhibit anatase and rutile phases. The lattice parameters remain unchanged, independent of Cu2+ content. Diameter of TiO2 increased significantly with increasing concentrations of Cu2+. The investigated results indicate that a greater portion of the Cu2+ ions are well incorporated into the anatase and rutile TiO2 lattices. The stretching vibration frequencies of the interatomic bonds were calculated by the electronegativity principle. The calculated data were compared with infrared spectra. The results show that in the rutile and anatase phases, O atoms in the TiO2 lattice and some interstitial Cu atoms form Cu-O bond, and other substitutional Cu that replaces Ti atoms in TiO2 lattice form Cu-O bond with O atoms in the TiO2 lattice.